Ichon Solar Radio Spectrogaphic System and Development of its Operation Software - K. S. Cho; G. H. Lee; K.-S. Kim (Journal of Astronomy and Space Sciences, 1997)
A solar radio spectrograph for monitoring solar radio emission was installed at Ichon branch of Radio Research Laboratory in 1995. The spectrograph consists of three different antennas to sweep a wide band of frequencies in the range of 30MHz-2500MHz. We have developed the operating software for the acquisition and the analysis of solar radio data obtained by solar radio spectrograph in order to carry out active solar radio observational studies. It was found that by using our software, we could have very good solar radio data for a sequence of three TYPE III bursts observed on 4 Nov. 1997. In this paper, we show the radio spectrograph and the result of the observation by its operating software.